Development and Survivorship of Scirtothrips dorsalis Hood (Thysanoptera: Thripidae) in Different Growth Stages of Mango and Selected Weeds - Affandi, Affandi; dela Rosa Medina, Celia; Velasco, Luis Rey Ibanez; Javier, Pio Arestado; Depositario, Dinah Pura Tonelete (AGRIVITA, Journal of Agricultural Science, 2018)
The research objective was to quantify the development and survivorship rate of S. dorsalis in different phenological stages of mango and selected weeds. The research was conducted in the laboratory of PT. Trigatra Rajasa, Mango plantation in Ketowan, Arjasa, Situbondo, East Java, Indonesia from February to September 2015. The development and survivorship rate were done through observation of life span of S. dorsalis from egg to pupa. Analysis of Variance and Duncan Multiple Range Test (p = 0.05) with 5 replications were applied to ensure the significant differences among the treatments. The result showed that development and survivorship of Scirtothrips dorsalis were supported by mango flushes and flower as well as some weeds such as Leucania leucochepala, Ipomoea triloba, Achalypha indica, Desmanthus leptophyllus and Azadirachta indica as source of food. Achalypha indica was the most suitable host with development time (12.82 Â± 0.21 days) and survivorship (33 %). Weed Tridax procumbent, Momordica charantia and Mimosa pudica were unable to provide the living requirement for immature developmental stage of S. dorsalis.